A2BP1 gene polymorphisms association with olanzapine-induced weight gain. (September 2015) - Dong, Licai; Yan, Hao; Huang, Xuebing; Hu, Xiaofeng; Yang, Yongfeng; Ma, Cuicui; Du, Bo; Lu, Tianlan; Jin, Chao; Wang, Lifang; Yu, Hao; Dong, Zheng; et al.
Graphical abstract: Abstract: The ataxin-2 binding protein 1 ( A2BP1 ) gene is reported to be one of the susceptibility genes in schizophrenia, autism, and obesity. The aim of this study was to explore the association of A2BP1 gene polymorphisms with antipsychotic induced weight gain (AIWG) in Chinese Han population. Three hundred and twenty-eight patients with schizophrenia were followed-up for an 8-week period of treatment with olanzapine. The fasting weights of 328 patients were measured before and after the 8-week course of treatment. Four single nucleotide polymorphisms (SNPs: rs8048076, rs1478697, rs10500331, and rs4786847) of the A2BP1 gene were genotyped by polymerase chain reaction (PCR). We analyzed putative association of A2BP1 polymorphisms with AIWG of olanzapine using linear regression analysis and found that SNP rs1478697 was significantly associated with AIWG caused by olanzapine ( p  = 0.0012; Bonferroni corrected p  = 0.0048). The association was replicated in another independent sample including 208 first-episode and drug-naïve patients presenting with schizophrenia after a 4-week treatment with olanzapine ( p  = 0.0092; Bonferroni corrected p  = 0.0368; meta p  = 5.33 × 10 −5 ). To explore the biological plausibility of A2BP1 in the pathogenesis of AIWG, we made expression analyses and eQTL analyses; these analyses showed that A2BP1 was highly expressed in whole brain tissues using the HBT database, and that rs1478697 has an expression quantitative trait locus effect in human cerebellar cortex tissues using the BRAINEAC database ( p  = 2.50E−04). In conclusion, the rs1478697 in A2BP1 may be associated with AIWG induced by 8-week treatment with olanzapine.